POSTOPERATIVE SENSITIVITY IN POSTERIOR COMPOSITE RESIN RESTORATIONS: LITERATURE REVIEW - Santos Bispo, Miqueias; de Castro Mudo , Alana; Ferreira Pedrosa, Ricardo; Mendes Pontanegra, Romero Samarcos (Health and Society, 2023)
Composite resin restorations are part of everyday clinical practice, delivering aesthetic and long-lasting results, provided there is mastery of the technique and knowledge of dental materials. Among the main failures in composite resin restorations is postoperative sensitivity, which causes discomfort for both the patient and the dentist due to the need to redo the procedure. The aim of this study is to demonstrate, through the literature, the possible origins of postoperative sensitivity and to describe more effective methods to minimize it. A literature review was conducted, with a temporal focus on the last 10 years (2013–2023), where articles published on the topic were searched in the PubMed, Scielo, Google Scholar, Scribd, and Lilacs databases. Postoperative sensitivity occurs due to the movement of existing dentinal fluids in the dentin, caused by inadequate sealing of dentinal tubules. Procedure failure is associated with factors such as restorative technique, adhesive system, monomer conversion rate, and polymerization time, which can lead to postoperative sensitivity. Thus, postoperative sensitivity can be triggered by various factors during the clinical procedure, requiring attention at every stage of the restorative technique by the dentist